Preparação e caracterização de vidros foto-termo-refrativos no sistema GeO2 – LaF3 - Mendoza, Valentina Gacha (2021)
In this work, lanthanum fluorogermanate glasses were synthesized by the melt-quenching method. First, the vitreous domain of the system was determined (100 – X – Y)GeO2 – XLaF3 – YK2O with X equal to 10, 20, 25, 30, and 40% molar, and Y equal to 10, 15, and 20% molar. Thermal and structural analyses were performed using differential scanning calorimetry (DSC) and X-Ray diffractometry (XRD). In the system with 10% K2O, vitreous samples with up to 40% of LaF3 were obtained with precipitation of the crystalline phase LaF3 after heat treatment, while in the system with 20% of K2O, vitreous samples with up to 30% of LaF3 and preferential precipitation of the KLaF4 phase after heat treatment were found. The effect of LaF3 incorporation on structural evolution was investigated, and from 0 to 20% it acts as a network intermediary, while in higher concentrations, it behaves as a modifier, decreasing network connectivity. The system with 15% K2O was characterized, and representative samples were doped with silver ions (Ag+). The high tendency of silver ions to reduce and form metallic nanoparticles during sample synthesis was observed. In this sense, the experimental parameters, nature of the precursors, and adaptation of the compositions were investigated to obtain colorless samples for the evaluation of photosensitive properties. The samples obtained were irradiated with a UV lamp and heat-treated to assess the ability to control the photosensitive effect. Redox processes and precipitation of metallic silver nanoparticles were followed by UV – Visible absorption. Photoluminescence spectroscopy was used to identify the silver species present before and after UV and TT irradiation. The evolution of the emission bands as the excitation length increases confirms the existence of several species of silver within the glass. In the original sample, the presence of neutral Ag0 atoms and Ag2 and Ag4 clusters predominates, while in the sample exposed to UV light for 12 hours and heat treatment, the formation of charged molecular clusters and the agglomeration of ions in the form Ag+2 is evident. Finally, preliminary tests of sub-nanosecond pulsed laser irradiation (900 fs) operating at 532 nm suggest the possibility of surface micro structuring with spatially controlled local modification. This work presents the first photosensitivity phenomenon in germanate glasses containing LaF3, useful in the development of photo-thermo-refractive or photosensitive glasses with near-infrared applications.